Understanding the impact of COVID-19 on tobacco and nicotine use among young adults identified as sexual and gender minorities: a mixed methods approach. (4th May 2022) - Lipperman-Kreda, Sharon; Sanders, Emile; Kaner, Emily; Antin, Tamar M. J.
Abstract: We investigated the perceived impact of COVID-19 on changes in tobacco and nicotine (NT) use among sexual and gender minority (SGM) young adults. We used a mixed methods approach that included closed- and open-ended survey questions and in-depth interviews. Participants were 53 SGM young adults in California who reported current or past cigarette smoking. Of study participants, 63% ( n  = 33) reported any changes in their NT use, and of those, 60% reported initial increase of NT use. Content analysis of an open-ended survey question revealed three reported reasons for changes in NT use: (1) changes in routine activities (27%), (2) stress (46%), and (3) health (24%). Thematic analysis of qualitative interviews identified several related themes: (1) in discussions of increased NT use, stress and boredom/free time were important aspects of changes to daily routines, (2) fluctuations in NT use behaviors occurred over time, (3) reasons for NT changes were multiple and intertwined, and (4) NT use changes were shaped by experiences related to intersectional forms of structural and social stigmatization. Results reveal the dynamic and complex ways in which participants described their pandemic-related changes in NT use—nuance that is crucial for compassionate and participant-centered approaches to tobacco prevention and cessation.